KINO’S AND JAMAL’S STRUGGLE REFLECTED IN JOHN STEINBECK’S THE PEARL VS TURINO DJUNAEDY’S INTAN BERDURI - Irwan Sumarsono; Ima Masofa (Elite : English and Literature Journal, 2022)
This study is comparative literature that focuses on the differences and similarities of two literary works, namely John Steinbeck’s The Pearl and a movie production directed by Turino Djunaedy entitled Intan Berduri. The study analyzed the similarities and differences in these two different works by using American School theory. This research used a qualitative method which was based on library research. The results of this study can be formulated as follows: 1) Both have similarities in the characterization in which the main characters are poor families and they hope they can have a better life after they find the pearl, and both of them fail to get the great future. (2) Both have differences in the way the main characters find the pearl and how the story ends. The characters in The Pearl cannot move from the lower class into the upper one, but the characters in Intan Berduri have the experience to be the upper class although just for a temporary moment and then go back to their previous class.